Geología de los cuadrángulos de Río Pinquén (hojas 25t1, 25t2, 25t3, 25t4), Pilcopata (hojas 26t1, 26t2, 26t3, 26t4), Quincemil (hojas 27u1, 27u2, 27u3, 27u4), Masuco (hojas 27v1, 27v2, 27v3, 27v4) y Ayapata (hoja 28v1) - [Boletín L 39] - Chumpitaz Ramírez, Marco Antonio (2021)
40 páginas, 17 mapas